Study on the effect of curved fiber laying angle on the vibration free attenuation of composite laminates. (10th March 2023) - Wang, Haoyu; Yang, Mingguang; Chen, Haoran; An, Luling; Wang, Xianfeng; Liu, Chen; Ye, Fan
Abstract: Firstly, three groups of fiber curve laminates with different numbers of layers and different fiber curve angles were designed and prepared. A cantilever plate free vibration test was used to analyze the influence of the fiber curve angle on the vibration free attenuation characteristics of the laminates. The three groups of contrast test results show that the fiber curve angle has a significant effect on the loss factor of the laminate structure. When the angle change of the fiber curve was ±<45|60>, the loss factor of the laminates reached the maximum value, and the vibration damping performance of the laminates was the best. Secondly, modal tests were carried out on the laminates, the modeling and simulation of the variable stiffness laminate were completed, and the influence of the fiber curve angle on the natural frequency of the laminate was explored. The results showed that when the number of laminate layers was the same, the natural frequencies of the laminates first increased and then decreased with an increase in the fiber curve angle. The first three natural frequencies of the laminates reached the maximum value when the fiber curve angle was ±<45|60 > or ±<60|75>. Finally, it is concluded that when the fiber curve angle of the laminates varies between ±<45|60>, the damping ratio and the first three natural frequencies of the laminates reach the maximum value, and the vibration damping performance is the best.